Effect of Fruits Consumption on Malondialdehyde (MDA) Reduction Among Athletes: A Systematic Review and Meta-Analysis - Dewi, Kartika Indaswari; Sumarmi, Sri; Adiningsih, Sri (STRADA : Jurnal Ilmiah Kesehatan, 2021)
One of the most prominent health problems for athletes is excellent fitness; thus, to meet such conditions, training is carried out with High-Intensity Interval Training. However, if it is done excessively, negative effects such as oxidative stress may result. External antioxidant, such as fruits, is therefore needed to reduce oxidative stress. This study further aims to pore over the effects of fruit consumption on the decrease of the MDA level of athletes during the HIIT with systematic review and meta-analysis as the research designs. The data is obtained through literary studies: PubMed, Semantic Scholar, Google Scholar, Elsevier, BMC, and PMC-NCBI. Furthermore, seven articles are reviewed by utilizing the PICOS and PRISMA principles. The data are further processed by using the RevMan 5.4 software. The summary effect results in CI 95% = -2.19 [-3.09, -1.29], which implies that there is a significant effect of fruit consumption on the athletes’ MDA level.